Association of physical activity, muscular strength, and obesity indicators with self-concept in Chilean children - Ferrari, Gerson; Cofre Bolados, Cristian.; Suárez Reyes, Mónica.; Farías Valenzuela, Claudio Ítalo.; Drenowatz, Clemens; Marques, Adilson; Pizarro, Tito (ARAN Ediciones, 2022)
Objectives: the present study examined the association of physical activity, muscular strength, and obesity indicators with self-concept in Chilean children. Methods: this cross-sectional study included 1078 Chilean children (mean age: 9.1 years [standard deviation: 1.1]; 598 boys). Physical activity was evaluated using the Physical Activity Questionnaire for Older Children. Upper and lower limb strength was evaluated using a digital dynamom-eter and standing long jump performance, respectively. The general strength index was calculated based on z-score values. Obesity indicators used were height, weight, body mass index, and body fat. The self-concept test was used to determine the academic, social, emotional, family, physical self-concept dimensions and total self-concept of children. Results: the mean total self-concept was 3.3 (standard deviation: 0.5). Physical activity was associated with academic (β: 0.32; p = 0.03), social (β: 0.24; p = 0.04), family (β: 0.13; p = 0.01), physical (β: 0.46; p = 0.01) self-concept dimensions and total self-concept (β: 0.22; p = 0.01), regardless of sex and age. Upper limb strength and general strength index were negatively associated with academic self-concept dimensions (β:-0.02; p = 0.01 and β:-0.13; p = 0.02) and total self-concept (β:-0.04; p = 0.01). Body weight and body mass index were negatively associated with academic (β:-0.01; p = 0.01 and β:-0.01; p = 0.02) and physical self-concept dimensions (β:-0.03; p = 0.03). Conclusions: these findings suggest that physical activity is positively related with self-concept. Thus, physical activity and self-percept must be considered as an essential social cognitive perspective to provide suitable mental health in children.
Asociación de indicadores de actividad física, fuerza muscular y obesidad con el autoconcepto en niños chilenos
Keywords: Physical activity; Schoolchildren; Self-concept; Obesidad; Aptitudes físicas